2011
DOI: 10.1158/1535-7163.mct-10-1090
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the p53 Pathway in Neuroblastoma Cells Using the Small-Molecule MDM2 Antagonist Nutlin-3

Abstract: Suppression of p53 activity is essential for proliferation and survival of tumor cells. A direct p53-activating compound, nutlin-3, was used in this study, together with p53 mutation analysis, to characterize p53 pathway defects in a set of 34 human neuroblastoma cell lines. We identified 9 cell lines (26%) with a p53 loss-offunction mutation, including 6 missense mutations, 1 nonsense mutation, 1 in-frame deletion, and 1 homozygous deletion of the 3 0 end of the p53 gene. Sensitivity to nutlin-3 was highly pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 38 publications
(45 reference statements)
12
51
0
Order By: Relevance
“…Nutlin3a has been shown to activate p53-dependent growth suppression in neuroblastoma carrying wild-type (wt) p53 in vitro and in vivo (23,24). Evidence that defects in effector molecules downstream of p53 are remarkably rare in neuroblastoma leads further support to the strategy to restore the function of p53 in neuroblastoma (25). However, recent studies show that treatment with nutlin3a creates a selective pressure for p53 mutations in neuroblastoma and other types of cancer leading to nutlin3a resistance, which in some cases contributes to multidrug resistance (26,27).…”
Section: Introductionmentioning
confidence: 98%
“…Nutlin3a has been shown to activate p53-dependent growth suppression in neuroblastoma carrying wild-type (wt) p53 in vitro and in vivo (23,24). Evidence that defects in effector molecules downstream of p53 are remarkably rare in neuroblastoma leads further support to the strategy to restore the function of p53 in neuroblastoma (25). However, recent studies show that treatment with nutlin3a creates a selective pressure for p53 mutations in neuroblastoma and other types of cancer leading to nutlin3a resistance, which in some cases contributes to multidrug resistance (26,27).…”
Section: Introductionmentioning
confidence: 98%
“…Yan et al (17) recently demonstrated that the expression of both the wild-type and mutant tumor suppressor protein, p53, in various cancer cell lines are regulated by HDAC8. In this regard, we noted that SH-SY5Y and BE(2)-C cells express wildtype and mutant forms of p53, respectively (38). Given these facts, it appeared plausible that the p53 genotype was responsible for the above noted differential effects in two types of neuroblastoma cells.…”
Section: Effect Of Tm-2-51 On the Dissociation Off-rate Of A Substratmentioning
confidence: 82%
“…9). The molecular origin of the above selectivity lies in the p53-specific genotype of the above cells (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that MEFs lacking p19 and p21 are still sensitive to Nutlin‐3a, although loss of p21 appears to hinder the ability of Nutlin‐3a to induce permanent cell cycle arrest 22. Another study showed that loss of p19 potentiated Nutlin‐3a‐induced growth inhibition of neuroblastoma cells 30. Further, MDM2 overexpression reportedly enhances cell sensitivity to Nutlin‐3a 31.…”
Section: Discussionmentioning
confidence: 99%